Perkembangan Kajian Hadis di Era Digital - Shofiatun Nikmah (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2022)
The development of technology that moves massively has an impact on the development of Islamic scientific studies, especially in the field of hadith. Hadith is the most important requirement in studying Islamic values and laws that apply in society.This encourages scientists from both western and eastern researchers to make hadith more accessible. The study of hadith that is complicated as takhrij al-hadi>th, through digital media can be handled easily. The digitization of hadith is also increasingly on the agenda as a form of dynamic development in the study of hadith.This study aims to find out how the development of hadith studies in the digital era. The library research method with a phenomenological approach is the author’s choice to conduct this research.Because by using these methods and approaches, the author can get a complete understanding of the dynamics of the development of hadith studies in the digital era. The results of this study, it can be seen that the study of hadith has experienced significant developments in the digital space.Hadith researchers are now also able to more easily access hadith books and can perform takhrij hadith and their understanding through the books available in the digital space.Thus, complex Hadith Research works can be made easier and researchers can focus on more integrated Hadith studies.